Civil Servants and Bureaucratic Culture in Kwara State: A Historical and Institutional Analysis - Bamidele, AbdulRasheed Hamza (Kashere Journal of Politics and International Relations, 2025)
The civil service plays a vital role in the governance structure of modern states, acting as the administrative machinery through which government policies are formulated, implemented, and sustained. This article probes the historical and institutional culture of the Kwara State Civil Service. This paper uses secondary sources such as scholarly works and government records, the study traces the civil service’s evolution, revealing how colonial administrative legacies marked by centralisation, hierarchy, and procedural rigidity continue to shape its operations. Since Kwara State’s creation in 1967, its bureaucracy has largely retained the structures and values of the British colonial system, resulting in persistent challenges like inefficiency, weak accountability, and limited responsiveness. Despite several reform efforts, these issues remain deeply rooted. The article recommends key reforms to transform the civil service into a more effective institution. These include enhancing bureaucratic training, adopting merit-based recruitment and promotion, and promoting decentralisation. By resolving these structural and cultural weaknesses, the study argues that the Kwara State Civil Service can become a more dynamic and accountable driver of sustainable development.